2014
DOI: 10.1177/0004563214529261
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-resolution melting genotyping assay for the angiotensin I converting enzyme insertion/deletion polymorphism and establishment of genotype-specific reference intervals in a Danish population

Abstract: We have developed a simple and robust method for ACE genotyping and determined genotype-specific reference intervals for s-ACE concentrations in the Danish population. The new reference intervals may increase the value of s-ACE measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Herein, we provide evidence supporting the higher prevalence of DD genotype/D carriers of ACE I/D polymorphism in HF due to Chagas disease in a case-control study of a population from Northeast Brazil. It has been suggested that the DD genotype is associated with higher serum angiotensin (s-ACE) activity and, consequently, the conversion of angiotensin I to angiotensin II in different populations 22,23 . The genotype/phenotype correlation has been consistently associated with inflammation and tissue injury that, in turn, regulates cardiovascular risks, such as stroke or inflammatory diseases [19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, we provide evidence supporting the higher prevalence of DD genotype/D carriers of ACE I/D polymorphism in HF due to Chagas disease in a case-control study of a population from Northeast Brazil. It has been suggested that the DD genotype is associated with higher serum angiotensin (s-ACE) activity and, consequently, the conversion of angiotensin I to angiotensin II in different populations 22,23 . The genotype/phenotype correlation has been consistently associated with inflammation and tissue injury that, in turn, regulates cardiovascular risks, such as stroke or inflammatory diseases [19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the DD genotype is associated with higher serum angiotensin (s-ACE) activity and, consequently, the conversion of angiotensin I to angiotensin II in different populations 22,23 . The genotype/phenotype correlation has been consistently associated with inflammation and tissue injury that, in turn, regulates cardiovascular risks, such as stroke or inflammatory diseases [19][20][21][22][23] . Although our cohort comprises a small number of patients in each stage and our study lacks a confirmatory functional analysis, the results are consistent and report an increased frequency of DD genotype among stage C patients compared with stages A or B1 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rigat et al were the rst to describe a method for the detection of I/D polymorphisms using polymerase chain reaction (PCR) and agarose gel electrophoresis [1,2]. Other techniques including real-time polymerase chain reaction (RT-PCR) [3][4][5], high resolution melting (HRM) [6,5], polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) [7] and microchip electrophoresis (ME) system [8] have also been used to detect I/D polymorphism. However, these techniques require tedious experimental procedures and expensive and sophisticated instruments that may not be available in clinical institutions.…”
Section: Introductionmentioning
confidence: 99%